Towards Distribution Feeders Frequency Response Via Solid State Transformers - Chavez-Orostica, H; Fuentes-Parra, C; Riquelme-Vera, E (Institute of Electrical and Electronics Engineers Inc., 2020)
Although Solid State Transformers have shown to be improve energy quality in distribution systems, its massive integration is a risk for the frequency stability as they prevent the loads from providing inertia and frequency respond to the system. Synthetic or virtual inertia strategies have been proposed to solve this problems in the case of wind and solar converters, but they are not directly applicable to solid state transformers. This paper propose a simple control strategy based on loads dynamic, SST and power system dynamics to provide the solid state transformer with frequency response. Study cases are presented using an ERCOT power system model and a Serbian distribution feeder model to show numerical results. © 2020 IEEE.